3D STRCUTURAL MODELLING FOR PROCATECHUATE 3, 4 DIOXYGENASEFROM PSEUDOMONASCEPACIA BASEDONTEMPLATE OF M CHAIN FROM P. AERUGINOSA - D. JAYASREE; RAO, J.VENKATESHWARA; RAO, D. VENKATA KRISHNA; K. K. KUMAR; P. B. K. KISHORE; H. A. NAGARAJARAM; DEVI, Y.PRAMEELA; NARASU, M. LAKSHMI (The Bioscan, 2007)
The 3D model of Protocatethuate 3,4 dioxygenase beta chain from Pseudomonas cepacia was built, based on X-ray crystallographic structure of Protocatethuate 3,4 dioxygenase M chain from Pseudomonas aeruoginosa. Dioxygenase catalyses the cleavage of molecular oxygen with subse- quent incorporation of both oxygen atoms into organic substrates. Some of the dioxygenase from bacteria catalyse critical ring-opening step in biodegradation of aromatic compounds. These bacterial enzymes contain non- heme ferric iron as the sole cofactor. Protocatethuate 3,4 dioxygenase (3,4PCD) was one of such enzyme recognized which catalyses the intradiol cleavage of protocatechuic acid by oxygen to produce â- carboxy cis-cis-muconic acid. Studies on 3,4(PCD) found in Pseudomonas aeruginosa is an oligomer with relative molecular mass (587K). The ho- mology modelling is done based on the programmes to annotate protein sequence aligment with 3D structural features which helps to understand the conservation of amino acids in the specific local environment.